2019
DOI: 10.1016/j.jvb.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Academic career development: A review and research agenda

Abstract: We thank Clara Mildenberger and Laura Sturm for their help with the literature search.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 121 publications
4
63
0
3
Order By: Relevance
“…grants), publications and/or citations contribute to promotion, prestige, and income. A second dominant theme is gender [52,53]. The common assumption that women's careers in research are less likely than men's to resemble an uninterrupted linear pattern, due to women's typically larger share in care responsibilities, is both a rationale for and a finding of studies looking at gender in research career.…”
Section: Plos Onementioning
confidence: 99%
“…grants), publications and/or citations contribute to promotion, prestige, and income. A second dominant theme is gender [52,53]. The common assumption that women's careers in research are less likely than men's to resemble an uninterrupted linear pattern, due to women's typically larger share in care responsibilities, is both a rationale for and a finding of studies looking at gender in research career.…”
Section: Plos Onementioning
confidence: 99%
“…In 21 centuries, many studies related to career counseling and career education focus on assistance to career decision of college students (Farnia, Nafukho & Petrides, 2018;Fearon, Nachmias, McLaughlin & Jackson, 2018;Li, Ngo & Cheung, 2019;Penn & Lent, 2018;Zacher, Rudolph, Todorovic & Ammann, 2018). Career decisions are about the ability of an individual in dealing with the influence of various factors in the career decision-making process.…”
Section: Career Decision-making and Career-planning Coursesmentioning
confidence: 99%
“…Our study’s contributions are twofold: First, we extend previous research, which has consistently shown that universities are gendered institutions and that gender bias exists on several levels, hindering women from reaching tenure ( van den Brink and Benschop, 2012 ; Treviño et al, 2015 ; Conesa Carpintero and González Ramos, 2018 ; Lansu et al, 2019 ; Teelken et al, 2019 ). Second, we shed light on the previously neglected senior career stage, which has been described as opaque and predominantly associated with the male stereotype ( Bleijenbergh et al, 2012 ; Evans, 2017 ; Ooms et al, 2019 ; Zacher et al, 2019 ). Our findings offer practical implications for early career support as well as organizational initiatives for the selection, promotion, and development of (female) scholars that aim to contribute to further convergence toward gender balance in academia.…”
Section: Introductionmentioning
confidence: 98%
“…Overall, the perceived lack of fit between women and professorships results in disadvantages that hinders women from applying, being selected, or promoted to professorships ( Heilman, 2012 ; Zimmerman et al, 2016 ; Zacher et al, 2019 ). Not only do gender stereotypes result in negative expectations about a woman’s performance in those positions, but concurrently women themselves perceive a lower fit with professorships ( Knipfer et al, 2017 ; Ysseldyk et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation